ON THE PECULIARITIES OF THE PALEORELIEF STRUCTURES OF VOLCANIC UPLANDS: (on the pattern of Aragats massif) (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
Extraordinary diversity of physiographic conditions and complicated geological and tectonic structures are typical for volcanic structures that result in non-uniformly distribution of ground water resources and variety of its composition and mineralization. The thick volcanic blankets and streams covering the buried topography complicate ground water prospecting problems in volcanic regions in comparison with any other geologic regions. These circumstances complicate carrying out of hydrogeological (and engineering geological) works and it is necessary to apply other prospecting methods and first of all the geophysical ones. In the article have been discussed ground water resources evaluation and regularities of ground water run-off distribution on the pattern of Aragats volcanic upland. Inner and under lava water streams, buried watersheds have been distinguished. Compiled cartographic materials can be applied in ground water prospecting works in the areas of investigated river basins.
Keywords: Aragats massif; paleorelief structures of volcanic uplands; geological and tectonic structures